2017
DOI: 10.21833/ijaas.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting small and medium enterprises (SMEs) continuance intention to adopt e-commerce in Jordan

Abstract: E-Commerce plays important roles in developed and developing countries. Many SMEs in developing countries could benefit enormously from ecommerce for their business activities. Despite the availability of both broadband communication and multiple internet service providers (ISPs), the adoption rate is still very low as compared to other developing nations in the region. Data was collected from manufacturing SMEs in Jordan, using a survey method. A total of 210 data was obtained from respondents. Data was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…On the other hand, e-commerce plays a vital role in developing and developed countries and consequently Jordan's economy, a recent study by Hussein and Baharudin (2017, p. 115) found that the Internet plays an important role in small and medium businesses adapting e-commerce in Jordan. Also, it was found out that Internet technology that can be utilised in CRM significantly improve customer satisfaction, loyalty, retention and value (Nikhashemi et al , 2013).…”
Section: Internet Service Provider In Jordanmentioning
confidence: 99%
“…On the other hand, e-commerce plays a vital role in developing and developed countries and consequently Jordan's economy, a recent study by Hussein and Baharudin (2017, p. 115) found that the Internet plays an important role in small and medium businesses adapting e-commerce in Jordan. Also, it was found out that Internet technology that can be utilised in CRM significantly improve customer satisfaction, loyalty, retention and value (Nikhashemi et al , 2013).…”
Section: Internet Service Provider In Jordanmentioning
confidence: 99%
“…The manufacturing sector in Jordan contributes 24% to the GDP of the country. Thus, the manufacturing SMEs in Jordan are considered critical contributors to the economic growth of Jordan (Hussein & Baharudin, 2017).…”
Section: Discussionmentioning
confidence: 99%